Current Status of Inpatient Antibiotic Use At The National Hospital of Obstetrics and Gynecology and Solutions - Tu, Nong Manh; Thao, Cao Thi Bich; Tuan, Nguyen Huy; Huy, Phan Quang; Cong, Nguyen Van (International Journal of Scientific Research and Management (IJSRM), 2025)
Antibiotics are a group of drugs that play an important role in health care. They are a decisive weapon in the treatment of infectious diseases caused by bacteria. However, this group of drugs is currently the most abused group of drugs. The irrational use of antibiotics leads to many serious consequences, especially the increase in the rate of antibiotic resistance. The increasingly serious level of drug resistance affects the effectiveness of treatment, poor prognosis, high risk of death, prolonged treatment time, increased treatment costs, affecting the health of patients and the community. Using quantitative research methods, based on the database of antibiotic consumption and the number of days of hospitalization of patients in clinical departments and the entire hospital in the period of 01/2022 - 12/2024 stored in the internal software of the Department of Pharmacy and the General Planning Department, National hospital of obstetrics and gynecology (NHOG). The results showed that the parameters have important contributions to pharmacology and clinical pharmacy in Vietnam and are of global significance.